(untitled) (Contemporary Journal of Social Science Review, 2025)
Corruption remains a persistent global challenge that undermines governance, weakens institutional credibility, and exacerbates socio-economic inequality. While contemporary anti-corruption strategies predominantly rely on legal enforcement and regulatory mechanisms, their effectiveness is often constrained by insufficient attention to the ethical and moral dimensions of human behaviour. This study examines Islamic ethics (akhlaq) as a comprehensive moral framework for combating corruption and promoting social justice. Grounded in the principles of tawḥīd (divine unity), amānah (trust), and ʿadl (justice), Islamic ethics conceptualises corruption (fasād) not merely as a legal violation but as a moral and social disorder that disrupts the divinely ordained balance of society. Employing a qualitative, interpretive methodology, the study utilises textual analysis of primary sources, including the Qur’an and Hadith, alongside classical and contemporary scholarly literature. The analysis is guided by the framework of maqāṣid al-sharīʿah (objectives of Islamic law) and focuses on key ethical constructs such as taqwā (God-consciousness), accountability (ḥisāb), and public interest (maṣlaḥah). Comparative insights from contemporary case studies further contextualise the application of these principles within modern governance systems. The findings demonstrate that Islamic ethics offers a dual-layered approach to corruption control by integrating internal moral regulation with external institutional accountability. This integrated model addresses both the behavioural causes and structural manifestations of corruption, thereby contributing to the realisation of social justice. The study further argues that the operationalisation of Islamic ethical principles within modern governance frameworks requires institutional adaptation, political commitment, and societal internalisation of ethical values. This research contributes to the growing discourse on ethics-based governance by providing a normatively grounded yet analytically rigorous framework that bridges classical Islamic thought with contemporary anti-corruption strategies.